2015
DOI: 10.4187/respcare.04076
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Endotracheal Tube Connector Dead Space Improves Ventilation: A Bench Test on a Model Lung Simulating an Extremely Low Birth Weight Neonate

Abstract: BACKGROUND: The reduction of instrumental dead space is a recognized approach to preventing ventilation-induced lung injury in premature infants. However, there are no published data regarding the effectiveness of instrumental dead-space reduction in endotracheal tube (ETT) connectors. We tested the impact of the Y-piece/ETT connector pairs with reduced instrumental dead space on CO 2 elimination in a model of the premature neonate lung. METHODS: The standard ETT connector was compared with a low-dead-space ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Neonates are usually intubated with narrow ETTs and have secretions, both of which are well known factors increasing resistance. Moreover, device (e.g., connector, flow sensor) induced dead space has an additional effect on resistance (3,6). In the present study, we found that CSS connectors increased airway resistance in mechanically ventilated neonates when compared to standard connectors.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Neonates are usually intubated with narrow ETTs and have secretions, both of which are well known factors increasing resistance. Moreover, device (e.g., connector, flow sensor) induced dead space has an additional effect on resistance (3,6). In the present study, we found that CSS connectors increased airway resistance in mechanically ventilated neonates when compared to standard connectors.…”
Section: Discussionsupporting
confidence: 63%
“…Recently, Ivanov reported the importance of reduction in the instrumental dead space for improvement of ventilation in their bench study. The authors demonstrated when the dead space in ETT connectors was decreased artificial lung ventilation improved, even though a slight increase in airway resistance and work of breathing occurred (6). Authors commented on this conflicting finding as the increase in resistance and work of breathing may affect patients especially during weaning as the importance of reduction in the instrumental dead space during weaning was previously emphasized (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ivanov (2015), the loss of air in the equipment can interfere with the amount of gas exchange that is expected to occur. Even a loss of space that is too large can match the TV [29]. Thus, the SNGT requires an airbag with a volume smaller than the TV to allow for easier observation of airbag movement.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this problem, some clinicians shorten ETTs, which may improve the CO 2 elimination . The shorter‐ and/or wider‐ID ETTs reduce resistance and the shorter one reduces respiratory dead space, presumably leading to decreased work of breathing (WOB) in newborn babies . Mohr et al have recently conducted an in vitro study to quantitate the effect of ETT shortening on WOB in simulated neonatal and pediatric lung models.…”
Section: Introductionmentioning
confidence: 99%